Evaluasi Daya Gabung Persilangan Jagung dengan Metode Diallel - Tanty, Heruna (Bina Nusantara University, 2011)
Corn is one of the plants that people use for food. Therefore, to obtain a superior maize crop a research is required. The formation of hybrid maize varieties can be created through a series of crosses among tetua (the parent plant). This research is conducted for selecting tetua which can give good results based on testing the general affinity and specific affinity with Diallel analysis. General affinity indicates the suitability level of an elder for various crossing partners. While special affinity indicates a specific level of suitability partner. The data of general affinity and specific affinity test is obtained from the results of crossbreeding experiments using seven tetuas. To hold a faster and a more accurate analysis in calculating the general affinity and affinity cross plants, we use a computer system.